Comparison of the Fuel Properties of Nitromethane Emulsions in Diesel and Biodiesel Assisted by Microwave Irradiation and Magnetic Stirring. Issue 9 (1st September 2016) - Lin, Cherng-Yuan; Tsai, Chang-Ting; Chen, Li-Wei
Abstract : Microwaves are high-frequency electromagnetic waves that assist in the formation of emulsions by enhancing the transfer of both mass and heat between the dispersed and continuous phases of the emulsion. Nitromethane has been used to improve combustion, but it is not miscible with petroleum-derived liquid fuels. In this study, the fuel properties of two-phase emulsions of nitromethane droplets dispersed in a mixture of diesel and biodiesel prepared by microwave irradiation were analyzed and compared with those of emulsions prepared by magnetic stirring. The emulsions were composed of various mass compositions of nitromethane, diesel, and biodiesel. The experimental results show that the emulsions formed by microwave irradiation had superior fuel properties, including a higher kinematic viscosity, higher flash point, lower cold filter plugging point, and less carbon residue than the emulsions prepared by magnetic stirring. Microwave irradiation is a more effective method for the preparation of more stable emulsions containing a uniform distribution of smaller dispersed droplets. In addition, the flash point, heat of combustion, cold filter plugging point, and carbon residue decreased while the kinematic viscosity increased with the increase in the weight fraction of nitromethane in the two-phase emulsions. GRAPHICAL ABSTRACT: